Ca(BH4)2–Mg2NiH4: on the pathway to a Ca(BH4)2 system with a reversible hydrogen cycle. Issue 26 (14th March 2016) - Bergemann, N.; Pistidda, C.; Milanese, C.; Emmler, T.; Karimi, F.; Chaudhary, A.-L.; Chierotti, M. R.; Klassen, T.; Dornheim, M.
Abstract : The hydride composite Ca(BH4 )2 –Mg2 NiH4 transfers all boron to MgNi2.5 B2 upon dehydrogenation, avoiding boron sinks. The rehydrogenation to Ca(BH4 )2 was confirmed. Abstract : The Ca(BH4 )2 –Mg2 NiH4 system presented here is, to the best of our knowledge, the first described Ca(BH4 )2 -based hydride composite that reversibly transfers boron from the Ca-based compound(s) to the reaction partner. The ternary boride MgNi2.5 B2 is formed upon dehydrogenation and the formation of Ca(BH4 )2 upon rehydrogenation is confirmed.